Estimated versus achieved maximal oxygen consumption in severely burned children maximal oxygen consumption in burned children - Tapking, Christian (Burns, 2018)
Purpose - In burned children, exercise training increases maximal oxygen consumption (VO2 max) and can be combined with the nonspecific beta-blocker propranolol to decrease cardiac work. VO2 max is estimated if indirect calorimetry is not available. We compared measured and estimated VO2 max in severely burned children treated with or without propranolol to determine the suitability of commonly used formulas in these populations. - Methods - Patients received propranolol or placebo (control) during acute hospitalization. VO2 max was measured during a modified Bruce treadmill test at discharge and compared to values obtained using the Cooper, Bruce, American College of Sports Medicine, and Porro formulas. Pearson correlations and Bland-Altman analyses were used to compare measured and estimated values. - Results - Ninety-nine children (propranolol n=46,control n=53) admitted at our facility between 2003 and 2016 were analyzed. Age at burn (propranolol 12±4years, control 12±3years,p=0.893) and total body surface area burned (propranolol 44±15%,control 49±14%,p=0.090) were comparable between groups. Measured VO2 max was higher in the propranolol group (25.5±6.0mL/min/kg vs. 22.0±4.7mL/min/kg,p=0.002) and was generally lower than estimated values. Age, sex, inhalation injury, body mass index, exercise time, and maximal speed were predictive of measured VO2 max in the control group. Age, sex, and maximal speed were predictive in the propranolol group. Backward selection yielded the formula [7.63+ 2.16×sex(females=0,males=1)+0.41×age(years)+0.15×maximal speed(m/min)] (R2=0.6525). - Conclusions - Propranolol seems to have beneficial effects on cardiorespiratory capacity in burned children. However, estimated VO2 max with common formulas were too high. The VO2 max formula reported here is suitable for propranolol-treated children and the Porro formula for non-propranolol-treated children.
Gesehen am 09.05.2019